A EAFM (Ecosystem Approach to Fisheries Management) Social Domain Assessment at The Fishing Base of Lampu Satu Coast, Merauke - Amir, Astaman; Welliken, Marius Agustinus (Hasanuddin University, 2025)
The social domain is one of the important domains in EAFM (Ecosystem Approach to Fisheries Management), which has the aim of ensuring the social welfare of fisheries communities such as high participation of stakeholders, minimal social conflicts in fisheries communities, and high utilisation of local knowledge in managing fisheries resources. This study aims to assess the status of stakeholder activeness, Fisheries Conflict Status and Existence Status and the effectiveness of local knowledge application in fisheries resource management based on EAFM social domain. This research was conducted at the fishing base of Merauke light beach one in 2024. The population in this study were fisheries communities and stakeholders in fisheries management. Sample withdrawal based on Roscoe as many as 34 respondents. Data analysis method using EAFM indicator domain assessment was analysed using multi criteria analysis (MCA) approach, which is an approach to convert qualitative data into quantitative. The results showed that stakeholder activeness was at poor criteria and given a red flag, Fisheries Conflict was at poor criteria and given a red flag, the existence and effectiveness of the application of local knowledge was at moderate criteria and given a yellow flag